Stereospecific/stereoselective nickel catalyzed reductive cross-coupling: An efficient tool for the synthesis of biological active targeted molecules - Uzma Afzal; Muhammad Bilal; Muhammad Zubair; Nasir Rasool; Syed Adnan Ali Shah; Zainul Amiruddin Zakaria (Elsevier B.V., 2023)
Reductive cross-electrophile transformations have recently been made into a robust and long-lasting synthetic technique for the production of specific CAC bonds. The use of inexpensive and plentiful electrophiles eliminates the need for pre-formation and handling of organometallics. In stereospecific reductive cross-coupling, nickel is one of the most cost-effective and flexible transition metals. This paper examines current developments in nickel catalyzed reductive cross coupling reactions and their potential application for the synthesis of biologically active molecules over the previous nine years.